Aligning ambulance dispatch priority to patient acuity: A methodology. (19th September 2018) - Andrew, Emily; Jones, Colin; Stephenson, Michael; Walker, Tony; Bernard, Stephen; Cameron, Peter; Smith, Karen
Abstract: Objective: In Victoria, Australia, Emergency Medical Service (EMS) demand has increased almost 5% per annum over the past 5 years. This may adversely affect response times to time‐critical patients. Additionally, >55% of cases have received Code 1 (lights/sirens) responses. Primary telephone triage occurs using the Medical Priority Dispatch System (MPDS); however, MPDS is reported to be highly sensitive, with common over‐triage. The present study describes the methodology applied to better align the response allocated to MPDS determinant codes with patient acuity. Methods: Data between October 2013 and August 2014 were extracted from the Ambulance Victoria data warehouse. The decision to allocate MPDS determinant codes to a lower response priority and/or secondary triage was based on epidemiological profiling and, in some cases, expert panel review. Results: The review identified 105 MPDS codes receiving a Code 1 response as suitable for a Code 2 (urgent) response, and 221 Code 1 or 2 codes as suitable for secondary triage. Data analysis estimated a reduction in Code 1 responses by 28%, and an increase in the secondary triage caseload by 120%. Modelling also predicted a 2.6 percentage point improvement in the proportion of Code 1 cases attended within 15 min. Conclusion: Analysis of a large EMS dataset supported changes to the EMS response priority for a number of MPDS determinant codes. Such changes should improve the alignment between EMS response and patient acuity, and improve response times to time‐critical patients. Other EMS with electronic data could consider testing this methodology.